2000
DOI: 10.1046/j.1471-4159.2000.0750436.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Proteasome Function in Alzheimer's Disease

Abstract: Inhibition of proteasome activity is sufficient to induce neuron degeneration and death; however, altered proteasome activity in a neurodegenerative disorder has not been demonstrated. In the present study, we analyzed proteasome activity in shortpostmortem-interval autopsied brains from 16 Alzheimer's disease (AD) and nine age-and sex-matched controls. A significant decrease in proteasome activity was observed in the hippocampus and parahippocampal gyrus (48%), superior and middle temporal gyri (38%), and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
559
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 756 publications
(598 citation statements)
references
References 28 publications
33
559
0
6
Order By: Relevance
“…Increased levels of protein carbonyls in the mutant transfectants could be related to impaired proteasomal function as well as to the observed rise in lipid peroxidation, because protein carbonyls can arise from direct oxidative damage to certain amino acid residues and/or by the binding of certain aldehyde end products of lipid peroxidation to proteins (22,58). Indeed, we reported marked increase in iron accumulation in the substantia nigra of AR-JP brains, indicating that oxidative stress appears to play an important role on nigral cell death in AR-JP (59).…”
Section: Discussionmentioning
confidence: 74%
“…Increased levels of protein carbonyls in the mutant transfectants could be related to impaired proteasomal function as well as to the observed rise in lipid peroxidation, because protein carbonyls can arise from direct oxidative damage to certain amino acid residues and/or by the binding of certain aldehyde end products of lipid peroxidation to proteins (22,58). Indeed, we reported marked increase in iron accumulation in the substantia nigra of AR-JP brains, indicating that oxidative stress appears to play an important role on nigral cell death in AR-JP (59).…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies from our group and others demonstrated that disturbance of proteolytic machinery is a key feature of degenerating neurons and appears in several neurodegenerative disorders (4,8,15). Proteasome activity was found to be reduced in AD brains than in age-matched controls (38,50) and also in DS brain (17). In addition, high levels of Ub were detected in brain and cerebrospinal fluid samples from AD patients (43).…”
Section: Innovationmentioning
confidence: 83%
“…Thus, oxidative inactivation of UCH-L1 possibly contributes to both protein aggregation and OS observed in AD brain. Moreover, UCH-L1 oxidative dysfunction could affect activity of the 26S proteasome, which is known to be altered in AD (221). Thus, these pathophysiological observations in AD brain may be related to oxidized UCH-L1: brain protein with excess ubiquitinylation, decreased activity of the 26S proteaome, and consequent accumulation of aggregated, damaged proteins.…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 99%